Implementation of vocational education in lower secondary school of male’ in republic of Maldives - Ibrahim, Abdulla (2023)
The skills of the Maldivians in the required fields are very important to develop the country. Until now, many skilled workers in the Maldives come from neighboring countries such as India and Sri Lanka. Therefore, a consistent and effective Technical and Vocational Education and Training (TVET) system is required to ensure the concept's success. This study aims to explore, understand, and explain the implementation of vocational education in Lower Secondary Schools of Male in the Republic of Maldives. A qualitative Fundamental Case Study research design was used in this study. A total of twelve (12) study participants were involved in this study. There are three (3) schools involved in this study which include three (3) principals, four (4) teachers, and five (5) students. The primary method of data collection is through interviews. The method of document analysis and observation is a method that supports the interview data. Findings are analyzed using the thematic method by understanding sentence segments and interpreting them into specific categories. These categories are analyzed and produce themes that help researchers develop conceptually. The finding shows that the concept, approach, implementation plan, impact on society, challenges, and relevance to higher education have been understood and referred to as a conceptual framework. Each of these components has its own elements that explain the implementation of vocational education in secondary schools. The framework also provides an overview of vocational education in secondary schools and can help schools to identify weaknesses in implementing vocational education and find strategies to address them. In conclusion, this research has provided valuable information about the implementation of vocational education in lower secondary schools in Male in the Republic of Maldives. The framework that was developed also acts as a guide for many parties to understand the vocational education system. The recommendation for the results of this study is to continue the study in a larger context and involve many other schools in the Maldives using different data collection and analysis methods. The results of this study can also be used to generate hypotheses for quantitative research as a continuation of the research.